2003
DOI: 10.1159/000070993
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Degradation Products in Peritoneal Dialysis: From Bench to Bedside

Abstract: In continuous ambulatory peritoneal dialysis patients, treatment success is inextricably linked to the functional and morphological integrity of the peritoneal membrane. This membrane, however, is repeatedly exposed to peritoneal dialysis fluids (PDFs) with unphysiological composition (e.g., acidic pH, high glucose content, hyperosmolarity). More recently, attention of researchers and clinicians has been focused on the presence of glucose degradation products (GDPs) that are generated during heat sterilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The GDPs in conventional PDF cause mesothelial injury and reduce mesothelial regeneration, hence predisposing the patient to peritoneal fibrosis (15). In addition, accumulation of AGEs in the peritoneal tissue correlates with the development of severe interstitial fibrosis and microvascular sclerosis in PD (2,16).…”
Section: Discussionmentioning
confidence: 99%
“…The GDPs in conventional PDF cause mesothelial injury and reduce mesothelial regeneration, hence predisposing the patient to peritoneal fibrosis (15). In addition, accumulation of AGEs in the peritoneal tissue correlates with the development of severe interstitial fibrosis and microvascular sclerosis in PD (2,16).…”
Section: Discussionmentioning
confidence: 99%
“…These fluids contain GDPs that are formed primarily during heat sterilization [20]. Several of these products have been identified and quantified [21] and, recently, 3,4‐DGE has been found to be the main candidate responsible for the clinical biocompatibility caused by conventional PDF [22]. Evidence has suggested that the mesothelial toxicity of PDF is related primarily to GDPs and not to glucose per se [23].…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of 3-deoxyglucosone, acetaldehyde, formaldehyde, methylglyoxal, glyoxal, furfural and 5-hydroxymethyl-furfural are significantly reduced when compared to standard PD fluids [65,67]. A summary of the numerous in vitro and in vivo experiments describing the beneficial effects of these new solutions is beyond the scope of this paper but can be found in several recent reviews [28,33,51,60,[68][69][70].…”
Section: Dialysate Glucose and Gdpsmentioning
confidence: 99%